Key Financial Ratios Drive Earnings Management in Indonesian Firms: Rasio Keuangan Utama yang Mendorong Manajemen Laba di Perusahaan Indonesia - Verdiana , Erisa Ghina; Hanif, Aisha (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of leverage, profitability, liquidity, total asset turnover, and free cash flow on earnings management in LQ45 index companies from 2019 to 2021. Using a sample of 23 companies selected through purposive sampling and analyzed with multiple linear regression via SPSS version 26, the results show that leverage, total asset turnover, and free cash flow significantly influence earnings management, while profitability and liquidity do not. These findings highlight key financial indicators that can signal earnings management practices, providing useful insights for investors, regulators, and auditors. Highlights: 1. Influential Factors: Leverage, asset turnover, and free cash flow affect earnings management.2. Non-influential Factors: Profitability and liquidity don't affect earnings management.3. Practical Use: Insights help investors, regulators, auditors detect earnings management. Keywords: Leverage, Profitability, Liquidity, Total Asset Turnover, Free Cash Flow